2022
DOI: 10.1681/asn.2021070948
|View full text |Cite
|
Sign up to set email alerts
|

Acute Treatment Effects on GFR in Randomized Clinical Trials of Kidney Disease Progression

Abstract: Background Acute changes in glomerular filtration rate (GFR) can occur following initiation of interventions targeting progression of chronic kidney disease (CKD). These acute changes complicate the interpretation of long-term treatment effects. Methods To assess the magnitude and consistency of acute effects in randomized clinical trials and explore factors that might affect them, we performed a meta-analysis of 53 randomized clinical trials for CKD progression enrolling 56,413 participants with at least one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Reducing glomerular hyperfiltration with dietary or pharmacological interventions can result in a negative acute effect on GFR in the short term, but in the long term, such interventions can stabilize GFR, as reflected by the chronic slope. 2,18,[20][21][22][23] This mechanism may lead to a negative correlation between the effect on the acute GFR slope and the effect on the chronic slope, in which case the clinical benefit of slowing decline in the chronic slope may be partially offset by the clinical implications of greater acute declines in GFR. Some have suggested that the inverse association between acute and chronic effects may be stronger for patients with more advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing glomerular hyperfiltration with dietary or pharmacological interventions can result in a negative acute effect on GFR in the short term, but in the long term, such interventions can stabilize GFR, as reflected by the chronic slope. 2,18,[20][21][22][23] This mechanism may lead to a negative correlation between the effect on the acute GFR slope and the effect on the chronic slope, in which case the clinical benefit of slowing decline in the chronic slope may be partially offset by the clinical implications of greater acute declines in GFR. Some have suggested that the inverse association between acute and chronic effects may be stronger for patients with more advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…Our acute studies in a 5/6 Nx model further showed that selonsertib does not acutely change GFR, renal blood flow, BP, or heart rate. Of note, both ACEI and sodium-glucose cotransporter-2 inhibitors are known to cause acute decreases in eGFR ("eGFR dip") due to acute lowering of systemic and/or glomerular hemodynamics, whereas selonsertib has also been shown to cause acute decreases in eGFR that are attributed to the inhibition of the tubular creatinine transporters MATE1/2K (22,23). Although these transporters do not have a prominent role in regulating plasma creatinine in rodents (24), this study and previously published studies demonstrating no effect on hemodynamics with selonsertib or ASK1 inhibition are consistent with the blockade of creatinine secretion as a cause for eGFR changes; however, more clinical studies are needed to fully address this.…”
Section: Discussionmentioning
confidence: 99%
“…Patterns of change in GFR (GFR slope) after initiation of an intervention are often nonlinear, with possibly differing direction and rates of changes in early follow-up (herein called acute slope) versus longer-term follow-up (herein called chronic slope) 39 . The average rate of decline from the beginning to the end of the study incorporates both elements (herein called total slope).…”
Section: Treatment Effects On the Gfr Slope And The Clinical Endpointmentioning
confidence: 99%